Implementation of Family Socialization Function in Shaping Children's Character in the Millennial Era - Meisyai, Reisti Siti; Herwina, Wiwin; Hamdan, Ahmad (Universitas Pendidikan Indonesia (UPI), 2024)
The formation of children's character has an important role for the family, parents should be able to pay attention, guide and provide direction to children when they start to grow up, which can be done by paying attention to the family's socialization function. In Rancabatu village there are still many parents who do not know the importance of the function of family socialization so that many parents are still indifferent to the formation of children's character, even though this function helps pay attention to the formation of children's character in this millennial era. The aim of this research is to determine the implementation of the family socialization function in shaping children's character in the millennial era. The method in this research uses descriptive qualitative methods, data collected is through observation, interviews and documentation. Data analysis begins with collecting data, reducing data, then presenting the data and then drawing conclusions. The research results obtained due to a lack of understanding regarding the importance of the family socialization function make parents pay less attention to the formation of their children's character, each parent has their own way of forming their child's character without paying attention to the socialization function. The condition of parents also influences the formation of children's character because there are parents who are indifferent and there are also those who are understanding. There are parents who try to be close to their children, there are also those who are just normal. Parental closeness has a significant impact on the child's growth and development. Family harmony and well-being are also influenced by the love and attention given to each child. In the millennial era, children's high work enthusiasm can also help them make friends and develop.